A mathematical model of type 1 diabetes involving leptin effects on glucose metabolism. (7th November 2018) - Kadota, Rei; Sugita, Kazuma; Uchida, Kenko; Yamada, Hitoshi; Yamashita, Masashi; Kimura, Hidenori
Highlights: A mathematical model of brain-centered glucoregulatory system is proposed. Effects of leptin on hyperglycemia are quantified. Leptin administration drastically improves insulin therapy. Abstract: Leptin, a hormone released from fat cells in adipose tissues, was recently found to be capable of normalizing glucose metabolism in animals. Clinical data on patients with lipodystrophy indicates that leptin may have a positive effect on glucose metabolism in individuals with diabetes. There are growing expectations that leptin can improve the current insulin treatment for patients with type 1 diabetes. We investigated this possibility through in silico experiments based on a mathematical model of diabetes, which is currently the only mode of research that eliminates human risk. A model of the brain-centered glucoregulatory system, in which leptin plays a central role, was constructed and integrated within a conventional model of insulin/glucose dynamics. The model has been validated using experimental data from animal studies. The in silico combination experiments showed excellent therapeutic performance over insulin monotherapy.